Adipocytes and Obesity-Related Conditions Jointly Promote Breast Cancer Cell Growth and Motility: Associations With CAP1 for Prognosis - Rosendahl, Ann H.; Bergqvist, Malin; Lettiero, Barbara; Kimbung, Siker; Borgquist, Signe (Frontiers in Endocrinology, 2018)
The global increase in overweight and obesity rates represent pressing public health concerns associated with severe comorbidities, amongst a rising incidence and impaired outcome of breast cancer. Yet, biological explanations for how obesity affects breast cancer are incompletely mapped. Herein, the joint impact by differentiated 3T3-L1 adipocytes and obesity-related metabolic conditions on breast cancer cells was evaluated in vitro and adipocyte-derived mediators assessed. Adipokine receptor expression was explored among breast cancer cell lines (n=47) and primary breast tumors (n=1,881), where associations with survival outcomes were investigated. Adipocytes and metabolic complications jointly stimulated breast cancer cell proliferation and motility, with phenotype-specific differences. Resistin was among the top modulated adipokines secreted by 3T3-L1 adipocytes under obesity-associated metabolic conditions compared with normal physiology. The newly identified resistin receptor, CAP1, was expressed across a large panel of breast cancer cell lines and primary breast tumors. CAP1 was associated with poor tumor characteristics with higher CAP1 expression among estrogen receptor (ER)-negative tumors, relative to ER-positive tumors (P=0.025), and higher histological grades (P=0.016). High CAP1 tumor expression was associated with shorter overall survival (adjusted hazard ratio [HRadj] 1.54; 95% confidence interval [CI], 1.11-2.13) and relapse-free survival (HRadj 1.47; 95% CI, 1.10-1.96), compared with low or intermediate CAP1 expression, particularly among ER-positive tumors or lymph node positive tumors. Together, these translational data demonstrate that the adipocyte secretome promote breast cancer cell proliferation and motility and highlight a potential role of CAP1 regarding breast cancer outcome – results that warrant further investigation to elucidate the obesity-breast cancer link in human pathology.